PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT SUARA BERSAMA, JAKARTA - Tajudin Tajudin; Taufik Supriadi (JURNAL MITRA MANAJEMEN, 2021)
AbstractThis study aims to determine the effect of work discipline and motivation on employee performance at PT. VOICE WITHJakarta. This research uses a quantitative approach with a survey method. The population is 60 employees of PT. Suara Bersama is part of the Jakarta project division with saturated sampling technique. Methods of data collection using a questionnaire with a Likert scale of 1 to 5. The method of data analysis using descriptive analysis with the help of software Excell and SPSS version 24.0. The results showed that (1) work discipline partially had a positive and significant effect on performance (2) motivation partially had a positive and significant effect on performance (3) Work discipline and motivation simultaneously had a positive and significant effect on performance. The implication is that to improve employee performance, it is necessary to increase work discipline and motivation through increased attendance monitoring with finger print and compensation policies in accordance with applicable regulations. Key words: work discipline; motivation; performance